Financial sustainability of higher education institutions in the Philippines: Issues, challenges, and opportunities - Connie Bayudan-Dacuycuy; Herisadel Flores; Arnel Onesimo Uy (Philippine Institute for Development Studies (PIDS), 2024)
Higher education institutions (HEI) and the quality of educational products and services they deliver play a critical role in supporting international development goals and Filipinos' national aspirations. However, achieving quality in tertiary education has benefits and costs, making HEI financial sustainability an important means to an end. This study adds to the scant literature on Philippine HEI financial sustainability, highlighting the key insight that HEI financial sustainability is an educational asset and strategic imperative. It forwards national and HEI-level policies to ensure that HEI can fulfill educational objectives, deliver valued outcomes, support societal advancement, and add tangible value to stakeholders.
Keywords: 330; financial sustainability; higher education institutions; revenue sources; financing strategies; risk management